Music from the air : digital theremin - Do, Thu Trang (Nanyang Technological University, 2020)
The Theremin is a musical instrument known for its unique method of playing that requires no physical contact. However, it can have a steep learning curve, and, in addition, a higher financial cost compared to other musical instruments. To shorten the learning curve and to introduce the possibility of playing the Theremin to more people, a digital Theremin utilising Leap Motion sensor, Microsoft Visual Studio .NET Framework and NAudio library was previously created by FYP Student Chock Zhong Cai which was further improved on by Associate Professor Alexei Sourin. Another FYP student Nihara Azeem made improvements to the application. This project made further improvements on the digital Theremin application by introducing new features that enhance the playing experience. These features include new sound effects, a learning mode that guides the user to play along with notes from MIDI files and lastly, the ability to record their playing. It also attempted to explore an alternative library for sound generation – Csound, whose results indicate moderate feasibility and possibility for future implementation.